Electrochemical reduction of oxygen-containing tungsten compounds in a molten eutectic mixture of sodium and calcium chlorides - Omel’chuk А.О.; Medvezhynska, O.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
Based on analysis of the results of voltammetric studies of the behavior of single crystalline tungsten and liquid gallium cathode, which contains WO3 or CaWO4, in the melt of a eutectic mixture of sodium and calcium chlorides and also by the composition of products that are formed at the cathode at different electrolysis potentials, it was found that the necessary condition for the electrochemical reduction of oxygen-containing tungsten compounds is potentiostatic electrolysis, which provides a compatible discharge of sodium and calcium cations. Oxygen- containing tungsten compounds are reduced not only by electric current, but also by sodium and calcium, which are released at the cathode during electrolysis. It is recommended to use calcium tungstate as a starting material for reduction. The reduction product is a fine-grained tungsten powder.